2019
DOI: 10.1007/s10637-019-00881-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cancer-associated thrombosis in patients undergoing treatment with immune checkpoint inhibitors

Abstract: Purpose Anticancer agents are known to increase cancer-associated thrombosis (CAT) onset. CAT onset rate is reported to be 1.92% in cisplatin-based therapy, 6.1% in paclitaxel plus ramucirumab combination therapy, and 11.9% in bevacizumab monotherapy. Because immune checkpoint inhibitors (ICIs) cause a sudden increase in T cell number, an association between administration of these drugs and increase in CAT incidence is likely. However, the extent to which ICI administration affects CAT incidence remains uncle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 33 publications
4
42
0
1
Order By: Relevance
“…Kunimasa et al 27 first described a single case of VTE in an individual treated with pembrolizumab. Ando et al 26 expanded on this report, describing VTE and ATE in 8.2% of a retrospective ll cohort of 122 individuals treated with pembrolizumab or nivolumab. Gutierrez-Sainz et al 34 described VTE in 16 of a cohort of 229 people with primarily lung cancers and melanoma over a median follow-up period of 9.8 months, and Moik et al 35 described a cumulative incidence of VTE and ATE in 12.9% and 1.8% of a cohort of 662 individuals with a median follow-up of 8.5 months.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Kunimasa et al 27 first described a single case of VTE in an individual treated with pembrolizumab. Ando et al 26 expanded on this report, describing VTE and ATE in 8.2% of a retrospective ll cohort of 122 individuals treated with pembrolizumab or nivolumab. Gutierrez-Sainz et al 34 described VTE in 16 of a cohort of 229 people with primarily lung cancers and melanoma over a median follow-up period of 9.8 months, and Moik et al 35 described a cumulative incidence of VTE and ATE in 12.9% and 1.8% of a cohort of 662 individuals with a median follow-up of 8.5 months.…”
Section: Discussionmentioning
confidence: 94%
“…[22][23][24][25] However, despite the expanding use of ICIs, there is little information available concerning their association with thrombosis. 26,27 Moreover, whether the occurrence of VTE in individuals receiving ICIs is associated with longer or shorter survival is unknown. We hypothesized that the pro-inflammatory effects of immunotherapy might initiate a thromboinflammatory response that augments the already elevated risk of VTE in malignancy 22,28 and therefore conducted a retrospective cohort study to determine the incidence of VTE in individuals with cancer receiving immunotherapy.…”
Section: Context and Significancementioning
confidence: 99%
“… 21 Rates of TE in our study are comparable to rates reported in other cancer types receiving ICI, which range from 2.6% to 5.2%. 14 22 Limited data are available for ATE. A large pharmacovigilance study demonstrated increased association of reporting cardiovascular events, like myocarditis, pericardial disease, and vasculitis with ICI, when compared with any drugs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reports ATE rate of 4.9% (6/122) and VTE rate of 4.1% (5/122) in patients with lung, stomach, or kidney cancer receiving ICI. 14 Three ICIs are approved by the Food and Drug Administration in melanoma, including ipilimumab (approved in 2011), nivolumab (2014), and pembrolizumab (2015). These agents can be given as monotherapy, or ipilimumab can be given in combination with nivolumab.…”
Section: Introductionmentioning
confidence: 99%
“…Currently available evidence on thromboembolic risks of ICI treatment is limited to small cohort studies and case reports, sometimes describing extreme hemostatic responses to ICI treatments, such as disseminated intravascular coagulation or hyperfibrinolysis. [7][8][9] Moik et al report a cohort of 672 patients treated with nivolumab, pembrolizumab, ipilimumab, atezolizumab, or avelumab with a median follow-up of 8 months. All patients were treated at a highly specialized cancer clinic, and nearly 15% were included in treatment studies, thus reducing the risk of unreported outcomes, despite the retrospective design of the analysis.…”
mentioning
confidence: 99%